Biotransformation of n-butanol to Fruity-Like Bio-Flavour by Indonesian Lactic Acid Bacteria - Setiyoningrum, Fitri; Adi, Deddy Triyono Nugroho; Priadi, Gunawan; Wibowo, Des Saputro; Octaviana, Senlie; Afiati, Fifi; Fidriyanto, Rusli; Prasetyo, Doni Dwi; Siregar, Abdul Rahman; Vincentlau, Dharma (Universitas Gadjah Mada, 2024)
Microbial production of aroma compounds is a promising alternative to extracting plants or chemical synthesis. In our research, the Indonesian lactic acid bacteria (LAB) have been utilised as producing fruity-like bio flavour by biotransformation approach using n-butanol as a precursor. The aims of our research are to identify LAB- secondary metabolites categorised fruity-like bio flavour and investigate the changes of glucose, mannitol, xylose, lactic acid and acetic acid in growth medium after fermentation. Our result research showed that n-butanol could be transformed to several fruity like bio flavour such as ethyl butyrate, butyl acetate, butyl formate, ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, 2-heptanone, butyl propanoate, butyl propanoate, butyl 2-methylbutanoate, butyl isovalerate, butyl pentanoate, and butyl hexanoate. All of LABs consumed above 75% of glucose and only Lactococcus lactis KGB1 consumed all the mannitol on fermentation medium. In addition, Lactococcus lactis KGB1 produced the highest xylose, 11.87 g/L LABs produced. Based on the amount of fruity-like bio flavour compound generated, Lactobacillus fermentum WKS2, Lactobacillus fermentum KGL2, Lactococcus lactis KK4, Lactobacillus fermentum WKS3, Lactococcus lactis KGB1, and Lactobacillus fermentum KGL7 could be considered as agent fruity-like bio flavour by biotransformation approach.